Osteoarthritis and ultra-distance marathon running - Leaver, Roy (MRC/UCT RU for Exercise and Sport Medicine, 2017)
Osteoarthritis (OA) is the most common degenerative joint disease. The impact loading on the articular cartilage of the large weight bearing joints (hip, knee, and ankle joints) during distance running might be a potential precipitating factor in OA. The aim of this case-control study was to investigate the relationship between total accumulated running volume and OA in the weightbearing joints. In this study, OA was defined as pain and/or stiffness and/or swelling in the weight-bearing and non-weight-bearing joints (wrists and fingers). The subjects for this study were selected from previous and current runners of the Two Oceans Ultra-marathon (56 km) in Cape Town (South Africa). The database (1356) consisted of all the runners who participated in this race between 1970 and 1983. From this data-base a random group of male runners (n =128) were divided into six 10-year age groups of runners (18 and 79 years). There was a random sample of 25 runners in five of these groups and three in the 70-79 year age group. Runners were age matched with a random sample of past pupils (n=204) of a school who were in their final year between 1923 and 1994. This was the control group. A questionnaire to diagnose OA was designed and validated with a sensitivity of 92% and a specificity of 71 %. The questionnaire was posted to the runners and controls. Incentive prizes were offered to improve the response rate, which was 59%. Completed information was obtained from 76 ultra-distance marathon runners (response rate 59%) and 114 controls (response rate 56%). In the control group there was a group who participated in running. This group was combined with the runners who were then divided into three groups according to their total running volume which was calculated by the following formula; years involved in running x months/year running x 4 x hours/week running. The subjects were thus divided into four groups: 1) controls (non-runners) (n=60), 2) low volume runners (n=43), 3) medium volume runners (n=43), and 4) high volume runners (n=44). Of these, 22 low volume runners, 7 medium runners, and 7 high volume runners stopped running. The prevalence (%) of OA in all groups was compared. The mean age of the control group was significantly higher than the three running groups. The mean height and weight of the medium volume group was significantly higher than the other groups. There was no significant difference in the BMI in each group. The frequency of professional and retired people was significantly higher in the control and each running group. A significantly greater percentage of controls had a history of admission to hospital. There were more controls on long-term medication, compared to runners. A significant number of injuries to the weight-bearing joints (specifically the knee joint) occurred in all groups, due to other sports (p =0.007). There were no significant differences in symptoms suggestive of OA in all groups when not adjusting for age and previous injuries. However, when assessing the odds ratio to determine the risk for OA in the weight-bearing joints, adjusting for age and previous injuries, the low volume group had the highest risk to develop OA (O.R. = 3.2, 95% C.I. = 1.0-10.3); the medium group had the second highest risk (O.R. = 1.7, 95% C.I. = 0.6- 4.8) and the high-volume group (O.R. = 1.1, 95% C.I. = 0.4-3.1) and control groups (O.R. = 1.0) had equally the lowest risk to develop OA. This study confirmed that distance running is unlikely to be a predisposing factor in the development of OA in the weight-bearing joints, even at high running volumes commonly seen in ultra-distance running.